A mathematical model for evaluating the effect of wind on downward-spraying rainfall simulators - Lima, J. L. M. P. de (2002)
Rainfall simulators are used to study a variety of different processes (e.g., water erosion, infiltration, overland flow, irrigation, movement of agrochemicals, etc.). Wind affects field experiments that make use of rainfall simulators. Water-drop trajectories and velocities are altered, affecting water application and kinetic energy distributions.